2015
DOI: 10.1021/acs.macromol.5b00857
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Ring Polymer Translocation through Nanopores

Abstract: We investigate the flow-induced linear and ring polymer translocation through nanopores using a hybrid simulation method that combines a lattice-Boltzmann approach for the fluid with a molecular dynamics model for the polymer chain. Our results illustrate that the critical velocity flux for the linear and ring chain exhibits characteristic differences: for the linear chain, the critical velocity flux is independent of the chain length, which is in agreement with previous work; whereas, for the ring chain, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 45 publications
7
37
0
Order By: Relevance
“…The sieving coefficients for the two plasmids are very similar for all values of the filtrate flux, with differences of less than 8% (except for a single data point at 40 μm/s for the Biomax ® 100 kDa membrane). Thus, the good selectivity for the supercoiled plasmids seen in [22] and experimental studies [23] have confirmed the universal transmission behavior of linear polymers with different chain length.…”
Section: Linear Plasmidssupporting
confidence: 56%
“…The sieving coefficients for the two plasmids are very similar for all values of the filtrate flux, with differences of less than 8% (except for a single data point at 40 μm/s for the Biomax ® 100 kDa membrane). Thus, the good selectivity for the supercoiled plasmids seen in [22] and experimental studies [23] have confirmed the universal transmission behavior of linear polymers with different chain length.…”
Section: Linear Plasmidssupporting
confidence: 56%
“…22,85,97 Yeomans et al and we also found that P(q)−q curve shows the smooth feature in simulation work. 26,86 However, Wu and Neel et al supported the opposite conclusion. 98,100 Note that there exists a similar debate when discussing the conformational transition in free flows.…”
Section: Progress In Experimental Observation Andmentioning
confidence: 98%
“…In the first mode, the chain end is put at the channel entrance first to form an initial deformation, 86,96 which makes it more popular in the past few decades due to a much shorter simulation time compared with the free capture mode. 26,37 In simulation, the pressure-driven flow can be implemented in the LB algorithm by introducing an external force density (F ext ), which plays the role of a body force. 26,86 For small Reynolds numbers, the velocity flow rate caused by applying external force density obeys a linear dependence (Darcy's law), q = k c F ext .…”
Section: Progress In Experimental Observation Andmentioning
confidence: 99%
See 2 more Smart Citations